Memaknai Studi Pergerakan Matahari dalam Perancangan Arsitektur: Kajian Beberapa Aplikasi Komputer Mengenai Studi Matahari - Tomasowa, Riva (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Investigating and rethinking process in academic world influenced the architectural design culture. Affordable supporting digital tools lead the unlimited exploration into new ideas and possibilities. Heliodon is one of the tools to represent the sun mobility that helps analyze architectural form finding process. The Sun evolution and revolution are mapped into a computerized framework. With this framework, vendors and research group can develope its capability to create a powerful exploration tool. This opportunity gives a redefined meaning of the design process where all information is exchanged digitally. This study discusses some applications such as Google Sketch Up, Rhino ceros with its Grasshopper plug-in, and Graphisoft ArchiCAD which record physical data of climatic factors, The aim of this paper is to describe how sun study in digital tools redefines the architectural design process.